MENINGKATKAN KEMAMPUAN KERJASAMA ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN KOOPERATIF TIPE TEAM GAMES TOURNAMENT - pasiningsih, pasiningsih (STAINU Purworejo, 2023)
The backgroundofthis research is the lack of activities that can stimulate children's cooperative abilities at the school. Increasing cooperation through cooperative play methods such as team tournament games is the right solution to stimulate children's cooperative abilities. A qualitative approach with the type of field research was used in this research. The data collection technique is observation, interviews and documentation. Meanwhile, data analysis techniques include data reduction or filtering, data presentation and conclusions. This research shows that it improves the cooperative abilities of children aged 5-6 years through cooperative play methods such as team games tournaments adapted to the RPPH theme using various games, namely: 1) floating and sinking object flows, 2) balloon relay, 3) hula hop jumping, 4) filling water in bottles, 5) blowing balls with straws, 6) puzzles, 7) clogs. In this research, there were also obstacles in improving children's cooperative abilities, namely that there were children who were individual, quiet, did not like group activities and chose friends when playing. In overcoming these obstacles, the solution used is to provide interesting group activities and the members are always replaced at each activity. Through the team games tournament activity, class B children are stimulated in their cooperative abilities so that children become more active, children do not choose friends, and children can complete group games well.